Comunicação, Valores Comunitários e Sustentabilidade: os portais da UMESP, FEI e FSA. - Rosa, Paulo Cezar (2009)
This work analyzes the relationship between communication and sustainability in community universities in the State of São Paulo which are part of the ABRUC (Brazilian Association of Community Universities). The objective is to examine the image of these universities, based on the communication strategies used in their institutional portals. It seeks to understand whether and how they use the fact that they are community universities as a means of differentiation in their institutional marketing. This research is qualitative, using Yin s (2005) methodology of multiple case study. Some aspects of Bardin s (2006) Content Analysis are also used, to categorize the terms that identify the community values. The portals of community universities located in the ABC region of São Paulo (Universidade Metodista do Estado de São Paulo UMESP, Centro Universitário Engenharia Industrial FEI and Centro Universitário Fundação Santo André FSA), constitute the main corpus of this research. The technique used to analyze the portals was structured based on the work of Vilella (2003). Aspects were evaluated relating to ease of navigation in the use of the information, namely: Usability, functionality and content. The data collection period was one month, distributed as follows: One week during the enrolment period for the university entrance exams, and three weeks at the start of the 2008 academic year. In the analysis of the construction of institutional image, it was also observed, based on the institutions economic and financial results, that there is a correlation between communication policy and financial sustainability. The main results were: a) there are no clearly visible community values in the institutional portals; b) the portals follow traditional patterns, without incorporating technological innovations that would guarantee visibility and transparency in the institutions actions; c) there is a correlation between the economic-financial results and the community differential as a communication strategy, and the sustainability of the institutions.(AU)